Konsep Solusi Lemah Pada Hukum Kekekalan Skalar Nonlinear - Maya Sari Syahrul; Dwi Sulistiowati (LPPM Universitas Dharma Andalas, 2022)
The conservation law states that the cumulative of a quantity in a closed system will stay remain unless there is an inflow or outflow that goes through the boundary area of the system. The law models a consevative phenomena from variety physical quantity that exist in nature. This study is an analysis of descriptive studies on the discontinuities propagation that arise in the nonlinear scalar conservation law with discontinuation initial value problem, also known as the Riemann problem, which is done using characteristic methods. As discontinuity shows, discontinue solution concept from conservation law is introduced , which is referred to as a weak solution.